The religious experience as "inner difference:" memory, childhood and exile in the last dictatorships in Argentina and Uruguay (Tempo e Argumento, 2023)
This article explores, from a biographical perspective, the memories of those who had the experience of being children during the forced exile in the last dictatorships in Uruguay and Argentina. I try to provide, from the focus on the experiences around religion that are recalled, a contribution to a subject that is poorly explored such as the memories of those who experienced exile during childhood. The paper intends to investigate the childhood memories that accommodate the making of a biographical experience, around difference as a feature. To do this I retrieve, from biographical narratives, scenes that shed some light on religion as a terrain where tensions between what is familiar and what is strange take place.
Keywords: childhood; memory; religion; exile